Design and implementation of a responsive website for EEE freshman to better transit into university - Wun, Elizabeth Soen Yeen (2019)
University life has never been easy. There are so many aspects in a student’s university life that sometimes can be too overwhelming for one to juggle and this is especially so for incoming freshmen. To achieve success in academic performance in school as well as one’s overall university experience, it all begins with having a good transition into university. In this project, a responsive website, survivEEE, was designed and implemented with the aims to serve as a helpmeet for EEE freshmen. It not only aims to provide them with essential resources they need for their first year, but also have an avenue to ask questions and foster a close-knit community within the school. With this university guide, freshmen from the School of EEE would be provided with a onestop platform to have easy access to guides on how to do course registration, examinations, or any generic information about the school. Not only that, they would have access to useful tools such as GPA calculator, scheduler, campus map and a forum.